KONSEKUENSI YURIDIS TINDAK PIDANA PENCURIAN OLEH ANAK PASCA DIKELUARKAN PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 MENGENAI PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAM KUHP - Noor Azizah (Al-Adl : Jurnal Hukum, 2017)
AbstractCase of the theft crime by the child is a law crime that should be examined wisely, in other side that action is a criminal crime that should be punished, but in another side, Child Juvenile Justice Law no. 3 Year 1997 about Juvenile Justice said that when the crime was done by the kid so Child Juvenile Justice Law no. 3 Year 1997 on Juvenile Justice become Lex Specialist against the procedural law applicable at all of justice levels, however this provision face symmetrically with the Supreme Court Regulation no. 2 of 2012 Concerning Adjustment of Limit Crime and Number of Penalties in the criminal code which become the guidance for the judges in deciding cases of light criminal hearing so that such matter will bring legal problem in court for judges to decide criminal case of theft as criminal acts (Tipiring) where the perpetrators are children.Keywords: Theft Crime, Adjustment of the Criminal Act and Theft Crime Limit by the Child.